2022
DOI: 10.1038/s41586-022-05126-w
|View full text |Cite
|
Sign up to set email alerts
|

RASA2 ablation in T cells boosts antigen sensitivity and long-term function

Abstract: The efficacy of adoptive T cell therapies for cancer treatment can be limited by suppressive signals from both extrinsic factors and intrinsic inhibitory checkpoints1,2. Targeted gene editing has the potential to overcome these limitations and enhance T cell therapeutic function3–10. Here we performed multiple genome-wide CRISPR knock-out screens under different immunosuppressive conditions to identify genes that can be targeted to prevent T cell dysfunction. These screens converged on RASA2, a RAS GTPase-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 64 publications
(127 reference statements)
0
69
0
Order By: Relevance
“…For control TCR RNA-seq experiments (Figure S5C-E), a dataset from a manuscript recently accepted for publication was analyzed ( (Carnevale et al, 2022), GSE204862). For GD2 CAR validation experiments, edited cells were sorted for CAR+/TCR-expression on day 7 (single inserts) or on day 6 and day 14 (combo inserts) after electroporation.…”
Section: Rna-sequencing (Bulk Rna-seq)mentioning
confidence: 99%
See 1 more Smart Citation
“…For control TCR RNA-seq experiments (Figure S5C-E), a dataset from a manuscript recently accepted for publication was analyzed ( (Carnevale et al, 2022), GSE204862). For GD2 CAR validation experiments, edited cells were sorted for CAR+/TCR-expression on day 7 (single inserts) or on day 6 and day 14 (combo inserts) after electroporation.…”
Section: Rna-sequencing (Bulk Rna-seq)mentioning
confidence: 99%
“…CRISPR/Cas9 mediated gene ablation of inhibitory receptors induced in dysfunctional T cellsstarting with PD1 -has recently been attempted in clinical trials (Stadtmauer et al, 2020). Lossof-function screens continue to nominate perturbations that can increase T cell fitness such as knockout (KO) of Regnase-1 (Wei et al, 2019), Roquin (Zhao et al, 2021a), Ptpn2 (LaFleur et al, 2019), SOCS1 (Sutra Del Galy et al, 2021) or RASA2 (Carnevale et al, 2022;Shifrut et al, 2018), in murine and/or human T cells. Third, large-scale gain-of-function screens using either CRISPR activation (CRISPRa) (Schmidt et al, 2022) or a lentiviral library of open reading frames (ORFs) have revealed promising perturbations such as overexpression of lymphotoxin B receptor (LTBR) (Legut et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, p38 inhibition improved the persistence and antitumor efficacy of CAR-based adoptive immunotherapies [ 191 ]. Similar screening studies have also been related to T cell proliferation, cytokine regulation, and tumor cell resistance, but these studies differed in biosample types, library sources, sgRNA numbers, and screening protocols (Table S1) [ 192 194 ].…”
Section: Strategies For Enhancing Car-t Cell Function By Genetic Mani...mentioning
confidence: 99%
“…Other than PD-1 and TIM-3, Carnevale et al ( 50 ), identified a novel immune checkpoint, RAS P21 Protein Activator 2 (RASA2), in T cells. RASA2 is a RAS GTPase-activating protein and is upregulated upon chronic stimulation.…”
Section: Approaches To Mitigate the Immunosuppressive Tumor Microenvi...mentioning
confidence: 99%
“…RASA2 is a RAS GTPase-activating protein and is upregulated upon chronic stimulation. As demonstrated in multiple murine models including leukemia, CD19-CAR-T cells with RASA2-ablation experience increased RAS/MAPK signaling and activation, leading to enhanced and persistent anti-tumor activity ( 50 ).…”
Section: Approaches To Mitigate the Immunosuppressive Tumor Microenvi...mentioning
confidence: 99%